2021
DOI: 10.3389/fcell.2021.795838
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Function by the Actin Cytoskeleton

Abstract: The regulatory role of actin cytoskeleton on mitochondrial function is a growing research field, but the underlying molecular mechanisms remain poorly understood. Specific actin-binding proteins (ABPs), such as Gelsolin, have also been shown to participate in the pathophysiology of mitochondrial OXPHOS disorders through yet to be defined mechanisms. In this mini-review, we will summarize the experimental evidence supporting the fundamental roles of actin cytoskeleton and ABPs on mitochondrial trafficking, dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 127 publications
1
26
0
Order By: Relevance
“…Furthermore, our data demonstrated that the F-actin stabilizer jasplakinolide alleviates βII spectrin de ciency-induced mitochondrial dysfunction and apoptosis, suggesting that βII spectrin regulates mitochondrial function by stabilizing F-actin. It has been established that F-actin localizes to mitochondria 40 . Most previous studies on the regulation of mitochondrial function by F-actin have focused on F-actin localization outside mitochondria to mediate mitochondrial dynamics 41,42 , tra cking and autophagy 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data demonstrated that the F-actin stabilizer jasplakinolide alleviates βII spectrin de ciency-induced mitochondrial dysfunction and apoptosis, suggesting that βII spectrin regulates mitochondrial function by stabilizing F-actin. It has been established that F-actin localizes to mitochondria 40 . Most previous studies on the regulation of mitochondrial function by F-actin have focused on F-actin localization outside mitochondria to mediate mitochondrial dynamics 41,42 , tra cking and autophagy 43 .…”
Section: Discussionmentioning
confidence: 99%
“…TQ significantly increased the expression of ACTB and BAG1 in both cell lines. Perhaps beta-actin helps to initiate apoptosis by allowing cytosolic pro-apoptotic proteins to be carried to mitochondria by a cytoskeleton-driven trafficking system [ 124 ]. Previous research has shown that actin can be used as a substrate for caspase cleavage in mammalian cells [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…MtDNAs have historically been assumed to be selectively neutral (Galtier et al, 2009 ; Immonen et al, 2020 ). However, accumulating information shows that this molecule may be under strong selection for ecological adaptation (Zhan et al, 2004 ; Immonen et al, 2020 ), consistent with its involvement in the differentiation, information transmission and apoptosis of cells (Scheckhuber et al, 2007 ), regulation of body biomass (Illescas et al, 2021 ), response to environmental stresses such as pathogen resistance to host immunity (Bartelli et al, 2018 ) and pesticides, and we believe that natural selection for local adaptation also contributes to the spatial distribution of mtDNA observed in P. infestans . Our argument is supported by several lines of evidence as listed below.…”
Section: Discussionmentioning
confidence: 80%